Nasab Anak di Luar Perkawinan Perspektif Hukum Progresif dan Maqāṣid Sharī’ah - Irzak Yuliardy Nugroho; Achmad Safiudin (State Islamic University (UIN) of Sunan Ampel, 2021)
The granting of rights in civil relations for children born out of wedlock with their biological fathers can be regarded as an effort to protect children's rights as human beings or citizens. Legislation should exist to protect children's human rights as legitimate children. Article 2 Paragraph (2) and Article 43 Paragraph (1) of Law no. 1 of 1974 concerning Marriage is considered to cause legal uncertainty, which results in loss of marital status and the legal status of children born outside of marriage according to the law. On the other hand, the shari'ah rules relating to the validity of Marriage and civil relations, including lineage, guardianship, inheritance, are expressly regulated by the shari'ah, carried out and internalized in their implementation. This study aims to analyze how the rights of children outside of Marriage in the decision of the Constitutional Court Number 46/PUU-VIII/2010 from the perspective of Progressive Law and how the lineage rights of children outside of Marriage according to maqāsid-al-sharī'ah. This study uses a qualitative method with a juridical-normative approach. The object of this research study is Constitutional Court Decision No. 46/PUU-VIII/2010. The Constitutional Court's decision caused the child's civil rights to be strengthened in the eyes of the law to reflect the application of progressive legal principles. Based on the maqāṣid-al-sharī'ah perspective, the Constitutional Court's decision that defends the rights of children outside of Marriage can be categorized as protecting the soul, which includes maṣlaḥah ḍarūriyah.